2016
DOI: 10.1021/acsphotonics.6b00463
|View full text |Cite
|
Sign up to set email alerts
|

Gold Nanoparticle-Based Terahertz Metamaterial Sensors: Mechanisms and Applications

Abstract: Terahertz (THz) waves, especially those assisted by THz metamaterials, have great potential for detecting trace amounts of sensing targets. Some nanomaterials, such as gold nanoparticles (AuNPs), also show promising characteristics; however, their application in this context is hindered by a lack of plasmonic activity in the THz region. This study is the first to introduce AuNPs into THz metamaterial applications as a new tool for improving the sensitivity of protein detection. We demonstrate the mechanism of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
81
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(82 citation statements)
references
References 36 publications
(55 reference statements)
0
81
0
1
Order By: Relevance
“…29 Alternatively, the high sensitivity of the metamaterial to the surrounding medium can also be exploited as an efficient sensing platform. [30][31][32][33] The enhanced sensitivity of the metamaterial comes from the strong confinement of electromagnetic fields in a subwavelength region and hence provides a pathway for reducing the analyte volume. This is extremely critical for sensing of biological molecules in aqueous solution, since THz absorption by water is significantly large and has been a challenge to THz spectroscopy for biological sensing.…”
mentioning
confidence: 99%
“…29 Alternatively, the high sensitivity of the metamaterial to the surrounding medium can also be exploited as an efficient sensing platform. [30][31][32][33] The enhanced sensitivity of the metamaterial comes from the strong confinement of electromagnetic fields in a subwavelength region and hence provides a pathway for reducing the analyte volume. This is extremely critical for sensing of biological molecules in aqueous solution, since THz absorption by water is significantly large and has been a challenge to THz spectroscopy for biological sensing.…”
mentioning
confidence: 99%
“…Ying and co‐workers and Ahmadivand et al demonstrated that AuNPs significantly increased the signal quality of THz metamaterials. As a result, the sensitivity and selectivity for specific targets were greatly enhanced . Another commonly involved nanomaterials in THz devices was the carbon nanomaterials, including graphene, single wall carbon nanotubes (SWCNTs), and multiwall carbon nanotubes (MWCNTs), etc .…”
Section: Microchip‐based Devicesmentioning
confidence: 99%
“…G) The regular reflective detection mode of terahertz metamaterials and Reflective curves resulting from different amounts of gold nanoparticles. Adapted with permission 16b. Copyright 2016, American Chemistry Society.…”
Section: Microchip‐based Devicesmentioning
confidence: 99%
“…Terahertz (THz) wave spectrum locates between the microwave and far infrared regions and becomes more and more attractive for various applications, including high-data-rate communication, bio-medicine imaging, immunosensing, security inspection, sensitivity-enhanced nuclear magnetic resonance (NMR), and so on [1][2][3][4][5][6][7][8][9]. Room-temperature efficient THz sources play key roles in developing THz technologies and applications.…”
Section: Introductionmentioning
confidence: 99%